Evaluation of some adhesive materials for repairing gypsum models - Radhwan H Hasan (University of Mosul, College of Dentistry, 2005)
Abstract The aim of this study was to evaluate some adhesive materials that are used in dentistry for repairing of gypsum cast. The specimens were prepared with dimensions 121×16×10 mm length, width and thickness, respectively. The total number of specimens was 96 (48 specimens for dental plaster, while the other 48 specimens were for dental stone). The length of each specimen was measured and recorded on its surface, then the specimens were fractured into two pieces and reattached together with one of the three adhesive materials, reattachment was done either immediately (time= 0) or after 4 minutes of adhesive application. These specimens were divided into six groups for each gypsum product, which involved: Group 1: Control, unrepaired specimens; group 2: Polycarboxylate cement, time= 0; group 3: Polyacrylic acid solution, time= 0; group 4: Polyacrylic acid solution, time= 4 minutes; group 5: Cyanoacrylate adhesive, time= 0; group 6: Cyanoacrylate adhesive, time= 4 minutes. The length of each specimen was measured again and differences in length for each repaired specimen was measured. Then all specimens were subjected to the flexure of transverse strength test. Data were analyzed using analysis of variance and Duncan's Multiple Range Test. The results indicated that using of cyanoacrylate adhesive, time= 0 and polyacrylic acid solution, time = 4 minutes had significantly higher transverse strength providing maximum adhesion for each gypsum product. The results of this study also showed that there were dimensional changes with polycarboxylate cement adhesive and such changes not observed with cyanoacrylate and polyacrylic acid solution adhesives